INCIDENCE OF POSTERIOR CAPSULAR OPACITY IN PATIENTS WITH INTRA OCULAR LENS WITHIN THE BAG VERSUS INTRA OCULAR LENS IN CILIARY SULCUS (Journal of Medical & Health Sciences Review, 2025)
Background: PCO is flagged as “The most common long-term complication of cataract surgery with intraocular lens (IOL) placement is posterior capsular opacity (PCO). The location of the IOL, either in the bag or even in the sulcus can also have an impact on the occurrence of PCO.Objective: To determine the rate of occurrence of posterior capsular opacity in patients receiving either cataract surgery with in-the-bag or sulcus intraocular lens implantation.Study Design and Setting: The study was a prospective cohort study that was done in Ophthalmology departments, Nishtar Hospital, Multan.Methodology: 162 patients that had undergone cataract extraction using IOL implantation were registered. Demographic, systemic comorbidities, and risk factors such as diabetes, hypertension, and smoking were documented. All the patients were categorized into two groups based on the IOL placement: in-the-bag and in the sulcus. PCO presence was determined at the 7 months end follow up. Chi-square test was used to analyze data with p 5 -1 being regarded as statistically significant..Results:The average age of the patients was 59.0 + 7.5 years, 46.3percent males and 53.7percent females. In total, 65 patients (40.1%) had PCO. PCO was also significantly prevalent in the sulcus group as compared to the in-the-bag group (50.6% vs. 29.6%; p = 0.01). Stratified analysis showed statistically significantly higher PCO in the sulcus group with all subgroups (patients aged 35-50 years) 47.5 vs. 27.5 (p = 0.04), diabetics (52.0 vs. 33.3; p = 0.01), hypertensives (54.8 vs. 32.3; p = 0.02), and smokers (52.2 vs. 33.3; p = 0.04).Conclusion:PCO was much more prevalent in Sulcus IOL implantation than in the-bag. IOL should be placed in the capsular bag to minimize the chances of posterior capsular opacity.